Determinants of Stunting among Children Aged 24–59 Months: The Role of Maternal and Infant Factors in Muara Papalik Subdistrict, Indonesia - Amelia Sari, Ayu Oktavia; Kalsum, Ummi; Asparian, Asparian; Eka Rini, Willia Novita; Dwi Fitri, Amelia; Muldiasman, Muldiasman (Rifa'Institute, 2026)
Introduction: Stunting remains a major public health problem, particularly in developing countries, including Indonesia. Despite a declining trend, its prevalence at the local level is still relatively high, indicating the presence of specific risk factors related to maternal and child conditions. Objective: This study aimed to identify maternal and infant factors associated with stunting among children aged 24–59 months in Muara Papalik Subdistrict, Tanjung Jabung Barat Regency. Method: A quantitative cross-sectional study was conducted among mothers with children aged 24–59 months. Data were collected through structured interviews and anthropometric measurements. Variables included antenatal care, maternal nutritional status, anemia during pregnancy, birth weight, exclusive breastfeeding, and early initiation of breastfeeding. Data were analyzed using univariate, bivariate, and multivariate logistic regression. Results and Discussion: Maternal and infant factors were significantly associated with stunting. Low birth weight, lack of exclusive breastfeeding, and poor maternal nutritional status were identified as key determinants. Birth weight was the most dominant factor influencing stunting. Conclusion: Stunting is influenced by combined maternal and infant factors, with birth weight as the strongest determinant. Improving maternal nutrition and promoting optimal infant feeding practices are essential to reduce stunting prevalence